Les Langues Néo-Latines (Boletín de la Societé des Langues Néo-Latines, Directora: Colette Pommier, 27 rue de la Chapelle, 75018, Paris, Francia), núms. 241 y 242, 1982. - Garavito, Julián (Thesavrvs, 2023)
Reseñas de revistas.